Resilience to Pain: A Peripheral Component Identified Using Induced Pluripotent Stem Cells and Dynamic Clamp - Mis, Malgorzata A.; Yang, Yang; Tanaka, Brian S.; Gomis-Perez, Carolina; Liu, Shujun; Dib-Hajj, Fadia; Adi, Talia; Garcia-Milian, Rolando; Schulman, Betsy R.; Dib-Hajj, Sulayman D.; Waxman, Stephen G. (The Journal of neuroscience, 2019)
Pain is a complex process that involves both detection in the peripheral nervous system and perception in the CNS. Individual-to-individual differences in pain are well documented, but not well understood. Here we capitalized on inherited erythromelalgia (IEM), a well characterized human genetic model of chronic pain, and studied a unique family containing related IEM subjects with the same disease-causing Na V 1.7 mutation, which is known to make dorsal root ganglion (DRG) neurons hyperexcitable, but different pain profiles (affected son with severe pain, affected mother with moderate pain, and an unaffected father). We show, first, that, at least in some cases, relative sensitivity to pain can be modeled in subject-specific induced pluripotent stem cell (iPSC)-derived sensory neurons in vitro ; second, that, in some cases, mechanisms operating in peripheral sensory neurons contribute to interindividual differences in pain; and third, using whole exome sequencing (WES) and dynamic clamp, we show that it is possible to pinpoint a specific variant of another gene, KCNQ in this particular kindred, that modulates the excitability of iPSC-derived sensory neurons in this family. While different gene variants may modulate DRG neuron excitability and thereby contribute to interindividual differences in pain in other families, this study shows that subject-specific iPSCs can be used to model interindividual differences in pain. We further provide proof-of-principle that iPSCs, WES, and dynamic clamp can be used to investigate peripheral mechanisms and pinpoint specific gene variants that modulate pain signaling and contribute to interindividual differences in pain. SIGNIFICANCE STATEMENT Individual-to-individual differences in pain are well documented, but not well understood. In this study, we show, first, that, at least in some cases, relative sensitivity to pain can be modeled in subject-specific induced pluripotent stem cell-derived sensory neurons in vitro ; second, that, in some cases, mechanisms operating in peripheral sensory neurons contribute to interindividual differences in pain; and third, using whole exome sequencing and dynamic clamp, we show that it is possible to pinpoint a specific gene variant that modulates pain signaling and contributes to interindividual differences in pain.